2019
DOI: 10.1167/19.7.16
|View full text |Cite
|
Sign up to set email alerts
|

Subtle predictive movements reveal actions regardless of social context

Abstract: Humans have a remarkable ability to predict the actions of others. To address what information enables this prediction and how the information is modulated by social context, we used videos collected during an interactive reaching game. Two participants (an “initiator” and a “responder”) sat on either side of a plexiglass screen on which two targets were affixed. The initiator was directed to tap one of the two targets, and the responder had to either beat the initiator to the target (competition) or arrive at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that adults predict the target of an action and make anticipatory eye movements to that location (Flanagan & Johansson, 2003). These predictions are likely based on kinematic cues (Cavallo et al, 2016;Diaz, Fajen, & Phillips, 2012) that are widely distributed across body of the actor (McMahon et al, 2019;Pesquita, Chapman, & Enns, 2016;Vaziri-Pashkam, Cormiea, & Nakayama, 2017). Adults can use this distributed information to make predictions even when the locus of the information is far from the body part performing the action.…”
Section: Action Prediction In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that adults predict the target of an action and make anticipatory eye movements to that location (Flanagan & Johansson, 2003). These predictions are likely based on kinematic cues (Cavallo et al, 2016;Diaz, Fajen, & Phillips, 2012) that are widely distributed across body of the actor (McMahon et al, 2019;Pesquita, Chapman, & Enns, 2016;Vaziri-Pashkam, Cormiea, & Nakayama, 2017). Adults can use this distributed information to make predictions even when the locus of the information is far from the body part performing the action.…”
Section: Action Prediction In Childrenmentioning
confidence: 99%
“…These cues begin early in the actor's movement. For example, when asked to predict the target of the reach, participants are able to predict the target of the reach before the actor's finger had even lifted-off from the table (McMahon et al, 2019). When the movements prior to the finger's lift-off are occluded, participants are much slower at predicting the target of the reach (Vaziri-Pashkam et al, 2017).…”
Section: Action Prediction In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that adults predict the target of an action and make anticipatory eye movements to that location ( Flanagan & Johansson, 2003 ). These predictions are likely based on kinematic cues ( Cavallo, Koul, Ansuini, Capozzi, & Becchio, 2016 ; Diaz, Fajen, & Phillips, 2012 ) that are widely distributed across the body of the actor ( McMahon, Zheng, Pereira, Gonzalez, Ungerleider, & Vaziri-Pashkam, 2019 ; Pesquita, Chapman, & Enns, 2016 ; Vaziri-Pashkam, Cormiea, & Nakayama, 2017 ). Adults can use this distributed information to make predictions even when the locus of the information is far from the body part performing the action.…”
Section: Introductionmentioning
confidence: 99%
“…These cues begin early in the actor's movement. For example, adults are able to predict the target of an actor's reach before the actor's finger had even lifted off from the table ( McMahon et al, 2019 ). When the movements prior to the finger's lift-off are occluded, participants are much slower at predicting the target of the reach ( Vaziri-Pashkam et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%